2018
DOI: 10.32504/hspj.v2i3.43
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh pendidikan kesehatan dengan media audiovisual dan media booklet terhadap perilaku caregiver dalam mencegah tuberkulosis pada anggota keluarga

Abstract: Pengaruh pendidikan kesehatan dengan media audiovisual dan media booklet terhadap perilaku caregiver dalam mencegah tuberkulosis pada anggota keluargaThe effect of health education with audiovisual media and booklet media on caregiver behavior in preventing tuberculosis in tamily members. ABSTRACTRecently, tuberculosis is still a global health problem in the world as well as in Indonesia. Millions of people die and contract tuberculosis every year. Various strategies and efforts are made to reduce the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
2
3
0
6
Order By: Relevance
“…Based on the results of the study, it was found that the difference in attitude scores in the control group and the intervention group showed that community-based health education treatment were effective in improving attitudes to prevent Covid-19. The results of this study are in line with research conducted by Syarif et al ( 2015) that health education using audio visual media can increase knowledge and behavior of clean and healthy lifestyle patterns in preventing TB transmission (Hartiningsih, 2018). Based on the research results, health education can improve the attitude of the intervention group.…”
Section: The Effect Of Community-based Health Education On Attitudes Of Covid-19 Preventionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the results of the study, it was found that the difference in attitude scores in the control group and the intervention group showed that community-based health education treatment were effective in improving attitudes to prevent Covid-19. The results of this study are in line with research conducted by Syarif et al ( 2015) that health education using audio visual media can increase knowledge and behavior of clean and healthy lifestyle patterns in preventing TB transmission (Hartiningsih, 2018). Based on the research results, health education can improve the attitude of the intervention group.…”
Section: The Effect Of Community-based Health Education On Attitudes Of Covid-19 Preventionsupporting
confidence: 90%
“…The results of this study are in line with the research that health education using audiovisual media can increase knowledge and behavior of hygiene and healthy living habits in preventing TB transmission (Hartiningsih, 2018). The results of this study are also supported by the level of education in the control group 1, most of them have a minimum of senior high education, where one of the factors affecting knowledge and attitudes is the level of education.…”
Section: The Effect Of Community-based Health Education On Attitudes Of Covid-19 Preventionsupporting
confidence: 87%
“…Hasil ini sejalan dengan penelitian Hartiningsih bahwa pendidikan kesehatan dengan media audiovisual dan media booklet dapat meningkatkan sikap anggota keluarga dalam pencegahan penyakit (Hartiningsih, 2018).…”
Section: Perbedaan Sikap Terhadap Program Kb Sebelum Dan Sesudah Inte...unclassified
“…Penelitian yang telah dilakukan sejalan dengan teori bahwa media audiovisual dapat melibatkan dua indra sebagai alat pembelajaran yaitu indra pendengaran dan penglihatan, sehingga semakin banyak alat indra yang terlibat untuk menerima dan mengolah informasi, semakin besar kemungkinan isi informasi dapat dimengerti dan dipertahankan dalam ingatan. 10 Selaras dengan penelitian yang dilakukan oleh Kristina, dkk bahwa pengetahuan pada kelompok yang mendapat pendidikan kesehatan dengan menggunakan media audiovisual sebelumnya akan mengalami perubahan yang bermakna. 11 McMichael menggambarkan pentingnya untuk lebih memahami hasil intervensi air, sanitasi dan kebersihan di sekolah yang terkait dengan penyakit dan pendidikan berbasis sekolah sehingga diperlukannya intervensi yang efektif.…”
Section: Pembahasanunclassified